Diseño de un sistema de monitoreo y notificación de incidencias en tiempo real utilizando software libre - Cassinelli Ramirez, Jose David (2015)
Monitoring systems are software that actively and passively will monitor all the components in a Data center, such as services, computers, switches, access points, UPS, power generator, cameras, etc. this is an essential part for having everything working correctlyin a Data Center that provides lots of services. In this paper I have proposed the design of a monitoring system using open source and the Simple network Management Protocol that will report real time incidents in different ways such as email or a mobile messaging client. The design of this monitoring system will be part of the Kishwar Project, a whole system that innovates the actual emergency system in case of an emergency that needs to evacuate people from a building, will do in a smart way. This monitoring system will constantly monitor cameras, processing servers, switches and everything that will be part of the emergency system . For this reason the design of a real time incident monitoring and notification system it’s necessary to complete the Kishwar Project and ensure proper operation of each of its parts.